The Impact of Occupational Safety and Health (OSH) Programs Hazard Report and Tahan Report on Reducing Workplace Accidents at PT Merdeka Tsingshan Indonesia - Ade Putra Niswan Makkasau; Ahmad Padhil; A. Dwi Wahyuni P (Candela Edutech Indonesia, 2025)
This study examines the influence of occupational safety and health (OSH) implementation through Hazard Report and Tahan Report programs on improving workplace safety culture and reducing occupational accidents at PT. Merdeka Tsingshan Indonesia. A quantitative approach was employed using a structured questionnaire distributed to company employees, with responses measured on a Likert scale. The collected data were analyzed using descriptive statistics, validity and reliability testing, and multiple linear regression analysis, including partial (t-test) and simultaneous (F-test) hypothesis testing. The findings indicate that the research instrument is both valid and highly reliable, with a Cronbach’s Alpha value exceeding the acceptable threshold. The coefficient of determination shows that approximately 65.4% of the variation in workplace safety culture can be explained by the independent variables, including employees’ understanding of hazard identification, implementation of reporting programs, compliance and participation levels, and program effectiveness. Furthermore, the results reveal that these variables have a statistically significant effect on safety culture, both individually and collectively. This study concludes that the implementation of Hazard Report and Tahan Report programs plays a crucial role in strengthening safety culture and contributes significantly to the reduction of workplace accidents, highlighting the importance of active employee involvement and consistent safety reporting systems in achieving effective occupational safety management.